Pengaruh iklim komunikasi dan promosi jabatan terhadap kinerja dan motivasi dengan disiplin dan kepuasan kerja sebagai variabel intervening - Sugeng Riski; Muslichah Erma Widiana (Penerbit Goodwood, 2020)
Purpose: Influence of communication climate and job promotion on employee performance and motivation with discipline and job satisfaction as intervening at PT. Japfa Comfeed Indonesia. Tbk in Gedangan Sidoarjo. The aim of this study is to test and analyze the influence of communication and promotion on employee motivation and performance with discipline and job satisfaction as variabels intervening at PT. Japfa Comfeed Indonesia. Tbk in Gedangan Sidoarjo Research methodology: The samples of this study are 74 respondents consisting of employees permanent of the division warehouse and production. This research applies path analysis by using the program of analysis Smart PLS. Results: The relationship between variables in this study produced thirteen hypotheses with significant influence and five hypotheses with not significant influence. Relation testing between organizational job promotion and motivation variabels has the biggest significance. Meanwhile, the relation testing between communication climate variabels and employee performance variabels has the smallest significance. Limitation: The limitation in this research is one company where the number of samples taken is only permanent employees of the warehouse and production only. Contribution: Results of this study are expected to be able to give contribution to human resources management and to practical management. Keywords: Communication climate, Job promotion, Employee Performance, Motivation, Discipline, Job satisfaction